PENGARUH TINGKAT KREATIVITAS TERHADAP KEMAMPUAN MEMBUAT SASTRA ANAK - Novy Trisnani; Wulan Tri Puji Utami (Universitas Sarjanawiyata Tamansiswa, 2022)
The development of creative thinking skills in student pedagogical activities can form a personality structure, which contributes to improving their professional culture and the effectiveness of the educational process. One form of stimulant that can be given to students is to make students creative in making children's literary works. The population in this study were 4th-semester students of the PGSD study program at IKIP PGRI Wates who took children's literature courses. This study aims to determine whether there is an influence of the level of student creativity on the ability to make children's literature. The influence of student learning creativity on the achievement of learning outcomes by 23% shows the tendency of the results of making children's literary works to significantly depend on the creativity of students. From the results of the study, it can be concluded that the higher the creativity of students, the higher the ability to make children's literature is achieved.